Fiber surface oxide layer and preparation method thereof

The ZrO2-RE2O3 interface layer was prepared on the surface of Al2O3 fibers by sol method, which solved the problems of uneven preparation and long time in the prior art, and achieved improvement in the absorption performance of the fibers and improved comprehensive performance, making it suitable for industrial production.

CN119121615APending Publication Date: 2024-12-13NORTHWESTERN POLYTECHNICAL UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411438919.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art has problems of relatively unevenness and long preparation time when preparing the ZrO2-RE2O3 interface layer, especially the method of preparing the interface layer on Al2O3 fibers has not yet been improved.

Method used

By using the sol method, the sol is prepared by adding citric acid to deionized water as a chelating agent, mixing zirconium oxychloride and rare metal nitrate, and soaking the Al2O3 fiber cloth in the sol, drying and curing and heat treatment to form a uniform ZrO2-RE2O3 interface layer.

Benefits of technology

The ZrO2-RE2O3 interface layer is uniformly and densely prepared on Al2O3 fiber, which improves the absorption and comprehensive performance of the fiber, and is suitable for laboratory research and industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121615A_ABST
    Figure CN119121615A_ABST
Patent Text Reader

Abstract

The invention discloses a fiber surface oxide layer and a preparation method thereof, and belongs to the technical field of inorganic material preparation. The preparation method comprises the following steps: adding citric acid as a chelating agent into deionized water, stirring, adding zirconium oxychloride.octahydrate and rare metal nitrate in the stirring process, and uniformly mixing to obtain sol; al2O3 fiber cloth is soaked in the sol, the soaked Al2O3 fiber cloth is dried and cured, the cured Al2O3 fiber cloth is subjected to heat treatment, and the Al2O3 fiber with the ZrO2-RE2O3 interface layer is obtained. According to the method, the sol is prepared, the preparation of the ZrO2-RE2O3 interface phase on the fiber can be realized, and the method for preparing the ZrO2-RE2O3 interface layer on the Al2O3 fiber is perfected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic material preparation, and in particular relates to an oxide layer on the surface of a fiber and a preparation method thereof. Background Art

[0002] Stealth technology is an important means of protection in modern warfare involving sea, land, air and space, and is an important technology to improve the survivability of aircraft on the battlefield. With the development of radar technology, aircraft have higher and higher requirements for the radar stealth performance of materials, and radar stealth technology has become the focus of the development of weapons and equipment in various countries. Oxide fiber reinforced oxide-based composite materials have the characteristics of low cost and oxidation resistance, and can be effectively applied to aircraft, especially aircraft tail nozzles in harsh service environments such as high temperature, high pressure, and oxidation. Among them, alumina fiber reinforced alumina-based (Al 2 O 3 f / Al 2 O 3 ) Composite materials have the characteristics of high melting point, low density, high strength, etc., and are ideal for structural / electromagnetic functional integrated materials suitable for harsh environments, but Al 2 O 3 It is a wave-transmitting material and does not have the ability to absorb waves, so it is necessary to add Al 2 O 3 f / Al 2 O 3 Add absorbent inside the composite material to enhance Al 2 O 3 f / Al 2 O 3 Microwave absorption properties of composite materials. Rare earth doped ZrO 2 Solid (ZrO 2 -RE 2 O 3 ) has been explored as a promising electrolyte material for solid-state batteries due to its high ionic conductivity and stability. 2 O 3 Add ZrO 2 -RE 2 O 3 , can improve Al 2 O 3 The dielectric properties of ceramics can also enhance the mechanical properties of composite materials, which provides an option for the selection of absorbing structural materials in aerospace and other fields.

[0003] Document 1 "Jing Zhang, Zhi-Gang Wang, Xiwen Song, et al. Tailoring the thermalconductivity of Sc 2 O 3-Yb 2 O 3 Co-stabilized ZrO 2 Thermal barrier materials and mechanism sight. Ceramics International, 2023, 49: 13601-13609. " reported that Yb was prepared by solid phase reaction sintering. x Sc y Zr 1-x-y O 2 (y=0.02, 0.04, 0.06; x+y=0.05, 0.06, 0.07) oxide ceramics. This method uses ZrO 2 , Sc 2 O 3 , Yb 2 O 3 The nanopowder is ball-milled, cold-pressed into blocks and then sintered at 1500°C to obtain the final oxide ceramic.

[0004] Document 2 "EELomonova, DAAgarkov, MABorika, et al.ZrO 2 -Sc 2 O 3 SolidElectrolytes Doped with Yb 2 O 3 or Y 2 O 3 .Russian Journal of Electrochemistry, 2020, 56(2): 118-123" Preparation of ZrO by directional crystal growth method 2 -Sc 2 O 3 -Yb 2 O 3 and ZrO 2 -Sc 2 O 3 -Y 2 O 3 ceramics.

[0005] Document 3 "Jiang Tan, Yuchang Su, Te Hu, et al. Preparation and conductivity of Sc 2 O 3 -CeO 2 -ZrO 2.Solid State Ionics, 2016, 292: 22-26. "Dissolving Sc by concentrated nitric acid 2 O 3 Get Sc(NO 3 ) 3 Solution, ZrOCl 2 8H 2 O、Sc(NO 3 ) 3 、Ce(NO 3 ) 3 6H 2 O, CO(NH 2 ) 2 The mixed solution having a cation concentration of 0.2 mol / L was obtained by mixing, and the solution was heated to obtain powder.

[0006] However, in the above preparation of ZrO 2 -RE 2 O 3 Among the methods, the solid phase preparation method has problems such as relatively unevenness, while the liquid phase preparation method has problems such as relatively long time. In addition, the above methods mainly focus on bulk ZrO 2 -RE 2 O 3 Preparation of Al 2 O 3 Preparation of ZrO on fiber 2 -RE 2 O 3 The interface layer method needs to be improved. Summary of the invention

[0007] In order to overcome the shortcomings of the prior art, the present invention aims to provide a fiber surface oxide layer and a preparation method thereof based on a sol method, wherein a sol is prepared to achieve ZrO 2 -RE 2 O 3 Preparation of interfacial phase.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] The present invention provides a method for preparing an oxide layer on the surface of a fiber, comprising the following steps:

[0010] S1: adding citric acid as a chelating agent to deionized water and stirring, and adding zirconium oxychloride octahydrate and rare metal nitrate during the stirring process and mixing them uniformly to prepare a sol;

[0011] S2: Al 2 O 3 The fiber cloth is immersed in the sol, and the Al2 O 3 The fiber cloth is dried and solidified, and the solidified Al 2 O 3 The fiber cloth is heat treated to obtain ZrO 2 -RE 2 O 3 Al in the interface layer 2 O 3 fiber.

[0012] In one embodiment, the rare metal nitrate is Sc(NO) 3 ·xH 2 O、Yb(NO) 3 ·5H 2 O and Y(NO) 3 6H 2 One or more of O.

[0013] In one embodiment, the mass ratio of the deionized water to the citric acid is 10:1-3.

[0014] In one embodiment, the amount of zirconium oxychloride octahydrate used is 4 to 16 g.

[0015] In one embodiment, the mass ratio of the zirconium oxychloride octahydrate to the rare metal nitrate is 10:1-3.

[0016] In one embodiment, the soaking time is 1 to 5 minutes.

[0017] In one embodiment, the drying and curing time is 2 to 4 hours; the drying and curing temperature is 70°C.

[0018] In one embodiment, the heat treatment temperature is 1100° C., and the heat treatment time is 2 hours.

[0019] The present invention also provides an oxide layer on the surface of a fiber obtained according to the above-mentioned preparation method. The oxide layer is ZrO 2 -Sc 2 O 3 -Yb 2 O 3 layer, ZrO 2 -Sc 2 O 3 -Y 2 O 3 Layer or ZrO 2 -Y 2 O 3 layer.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention provides a method for preparing an oxide layer on the fiber surface based on a sol method, wherein zirconium oxychloride, rare metal nitrate, citric acid and deionized water are used to prepare a rare metal hybrid zirconium oxide sol, and an alumina fiber cloth is immersed in the sol and subjected to heat treatment to form an oxide layer on the fiber surface. 2 O 3 Successful preparation of ZrO on fiber 2 -RE 2 O 3 The purpose of this method is to be able to 2 O 3 The introduction of absorbing phase into Al 2 O 3 The microwave absorption performance of the fiber is improved by providing a sol to introduce ZrO 2 -RE 2 O 3 The sol has citric acid as a chelating agent, deionized water as a solvent, zirconium oxychloride (ZrOCl 2 ) and rare metal nitrates (Sc(NO) 3 、Yb(NO) 3 、Y(NO) 3 ) as the solute to prepare a uniform sol. Wherein, by using citric acid as a chelating agent, a stable metal complex can be formed, and the addition of citric acid can adjust the hydrolysis and condensation rates of the solute and control the performance of the final oxide product. One focus of the present invention is that by using citric acid as a chelating agent, a sol is prepared, and this sol can further prepare an oxide interface. The above-mentioned sol can ensure that the solute is uniform and the preparation method is simple. The steps of sol configuration, fiber immersion, drying and solidification, and heat treatment are relatively simple, easy to control and repeat, suitable for laboratory research and industrial production, and the surface properties of the fiber can be changed through the design of the interface layer, which is convenient for further research on the modification of alumina fiber. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the microscopic appearance of the alumina fiber before the interface layer is attached;

[0023] Figure 2 This is a surface morphology of the fiber prepared in Example 1 of the present invention;

[0024] Figure 3 This is a surface morphology of the fiber prepared in Example 2 of the present invention;

[0025] Figure 4 This is a surface morphology of the fiber prepared in Example 3 of the present invention;

[0026] Figure 5 This is a surface morphology of the fiber prepared in Example 4 of the present invention;

[0027] Figure 6 This is a surface morphology of the fiber prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0029] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0030] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0031] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0032] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0033] The present invention provides a method for preparing an oxide layer on the surface of a fiber. The method is based on a sol-gel method and comprises the following steps:

[0034] S1: adding citric acid as a chelating agent to deionized water and stirring, and adding zirconium oxychloride octahydrate and rare metal nitrate during the stirring process and mixing them uniformly to prepare a sol;

[0035] S2: Al 2 O 3 The fiber cloth is immersed in the sol, and the Al 2 O 3 The fiber cloth is dried and solidified, and the solidified Al 2 O 3The fiber cloth is heat treated to obtain ZrO 2 -RE 2 O 3 Al in the interface layer 2 O 3 fiber.

[0036] The present invention provides a sol method for preparing an interface layer on the surface of an Al2O3 fiber, which is used to uniformly and densely prepare a ZrO2-RE3O3 (RE represents a rare earth element such as Sc, Yb, and Y) composite oxide layer on the surface of the Al2O3 fiber. The method uses citric acid as a key chelating agent, effectively promotes the stable dispersion of metal ions in the solution, prevents agglomeration and precipitation, and lays a foundation for the uniform formation of the subsequent oxide layer. By mixing zirconium oxychloride octahydrate with selected rare earth metal nitrates and soaking the Al2O3 fiber cloth, the sol is fully penetrated into the fiber surface, ensuring the uniformity of the coating.

[0037] The specific steps include:

[0038] Take 10g of deionized water, weigh it and add citric acid as a chelating agent, and start stirring, wherein the mass ratio of deionized water to citric acid is 10:1-3;

[0039] Weigh 4-16g zirconium oxychloride octahydrate (ZrOCl 2 8H 2 O), weigh rare metal nitrate (Sc(NO 3 ) 3 ·xH 2 O、Yb(NO 3 ) 3 ·5H 2 O and Y(NO) 3 6H 2 O), wherein the mass ratio of zirconium oxychloride octahydrate to the rare metal nitrate is 10:1-3, and zirconium oxychloride octahydrate and the rare metal nitrate are added into the deionized water and citric acid during stirring and mixed to obtain a sol;

[0040] Al 2 O 3 The fiber cloth is immersed in the prepared sol for 1 to 5 minutes. 2 O 3 The fiber cloth is dried and cured in an oven at 65-75°C for 2-4 hours, and the preferred drying and curing temperature is 70°C;

[0041] The solidified Al 2 O 3 The fiber cloth is heat treated at 1000-1200℃ for 2 hours to obtain ZrO 2 -RE2 O 3 Al in the interface layer 2 O 3 The fiber is preferably heat treated at a temperature of 1100°C.

[0042] The present invention provides a method for preparing an oxide layer on the surface of a fiber based on a sol method. First, citric acid is used as a chelating agent. Citric acid can effectively chelate metal ions to form a stable sol system. This helps to evenly distribute the metal ions in the solution and avoid agglomeration or precipitation in subsequent steps, thereby ensuring the uniformity and density of the oxide layer on the fiber surface. Secondly, zirconium oxychloride octahydrate and rare metal nitrates are mixed, and a composite oxide layer with specific composition and properties can be prepared by introducing rare metal nitrates (such as nitrates of Sc, Yb, and Y). These rare metal oxides often have excellent physical and chemical properties, such as high temperature stability, corrosion resistance, catalytic activity, etc., which can significantly improve the comprehensive performance of the fiber. Subsequently, Al is soaked 2 O 3 Fiber cloth, directly soaking the fiber cloth in the sol can ensure that the sol fully penetrates every surface of the fiber to form a uniform coating. This method is simple to operate, easy to control, and can achieve large-scale production.

[0043] Among them, the drying and curing process helps to remove the moisture and organic solvent in the sol, and transform the sol into a solid gel layer. Appropriate drying temperature and time can ensure the stability and density of the gel layer, laying the foundation for the subsequent heat treatment process. High-temperature heat treatment is a key step in forming a dense oxide layer. Through heat treatment, the organic matter in the gel layer is completely removed, the metal ions undergo oxidation reaction to generate oxides, and combine with each other to form a dense oxide layer. The choice of heat treatment temperature and time has an important influence on the structure and properties of the oxide layer, and needs to be optimized according to specific needs. The ZrO prepared above 2 -RE 2 O 3 (RE is a rare earth element) interface layer can significantly increase the Al 2 O 3 The fiber has high temperature resistance, oxidation resistance, corrosion resistance and mechanical strength, etc. The improvement of these properties makes the fiber have a wider application prospect in high temperature and harsh environment.

[0044] The present invention also provides a fiber surface oxide layer prepared according to the above-mentioned method for preparing an oxide layer on the fiber surface based on the sol method, wherein the oxide layer is ZrO 2 -Sc 2 O 3 -Yb 2 O 3 layer, ZrO 2 -Sc2 O 3 -Y 2 O 3 Layer or ZrO 2 -Y 2 O 3 layer.

[0045] By introducing an interface layer composed of oxides such as ZrO2, Sc2O3 and Yb2O3 or Y2O3, the electromagnetic parameters (such as dielectric constant and magnetic permeability) of Al2O3 fibers can be adjusted, thereby optimizing the impedance matching between the fiber and free space, allowing more electromagnetic waves to enter the material instead of reflecting on the surface, which is the key to improving the absorption performance. These oxide layers enhance the attenuation of electromagnetic waves through various mechanisms such as internal polarization, scattering, and interface reflection, thereby effectively reducing the transmission and reflection of electromagnetic waves and improving the absorption efficiency of the material. The introduction of ZrO2-Sc2O3-Yb2O3, ZrO2-Sc2O3-Y2O3 or ZrO2-Y2O3 layers can form a multilayer composite structure, which is conducive to multiple reflections and scattering of electromagnetic waves inside the material, further increasing the attenuation path and attenuation time of electromagnetic waves. The formation of an oxide layer may change the surface morphology of Al2O3 fibers, such as forming a rough surface, a microporous structure or a nanostructure. These structural features can increase the interaction area between electromagnetic waves and materials and improve the absorption performance. In addition, oxides such as ZrO2, Sc2O3, and Yb2O3 or Y2O3 all have high melting points and good thermal stability. Their introduction can significantly improve the thermal stability of Al2O3 fibers in high temperature environments, thereby broadening the application range of the material. These oxide layers can also improve the chemical stability of Al2O3 fibers to a certain extent, resist corrosion by corrosive media such as acids and alkalis, and extend the service life of the material.

[0046] In summary, ZrO2-Sc2O3-Yb2O3 layer, ZrO2-Sc2O3-Y2O3 layer or ZrO2-Y2O3 layer as the oxide layer on the surface of Al2O3 fiber has significant advantages in optimizing electromagnetic properties, improving thermal stability and chemical stability, and enhancing comprehensive performance, thereby effectively improving the microwave absorption performance of Al2O3 fiber.

[0047] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0048] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0049] Example 1

[0050] (1) Take 10 g of deionized water, start stirring, weigh and add 3 g of citric acid;

[0051] (2) Weigh 16 g of zirconium oxychloride octahydrate (ZrOCl 2 8H 2 O), 1.95 g of water and scandium nitrate (Sc(NO 3 ) 3 ·xH 2 O) and 0.25 g ytterbium nitrate pentahydrate (Yb(NO 3 ) 3 ·5H 2 O), adding to the product obtained in (1) and mixing uniformly to obtain a sol;

[0052] (3) Al 2 O 3 The fiber cloth is immersed in the prepared sol for one minute, and the Al 2 O 3 The fiber cloth was dried and cured in an oven at 70°C for 2 hours;

[0053] (4) The solidified Al 2 O 3 The fiber cloth was heat treated at 1100℃ for two hours to obtain ZrO 2 -Sc 2 O 3 -Yb 2 O 3 Al in the interface layer 2 O 3 fiber.

[0054] The fiber morphology obtained in this example is as follows Figure 2 As shown, compared to Figure 1 From the morphology of the original fibers, it can be clearly seen that the fiber surface is covered with a solid surface.

[0055] Example 2

[0056] (1) Take 10 g of deionized water, start stirring, weigh and add 3 g of citric acid;

[0057] (2) Weigh 16 g of zirconium oxychloride octahydrate (ZrOCl 2 8H 2 O), 2.19 g of water and scandium nitrate (Sc(NO 3 ) 3 ·xH 2 O) and 0.21 g yttrium nitrate hexahydrate (Y(NO) 3 6H 2 O), adding to the product obtained in (1) and mixing uniformly to obtain a sol;

[0058] (3) Al 2 O 3 The fiber cloth is immersed in the prepared sol for one minute, and the Al 2 O 3 The fiber cloth was dried and cured in an oven at 70°C for 2 hours;

[0059] (4) The solidified Al 2 O 3 The fiber cloth was heat treated at 1100℃ for two hours to obtain ZrO 2 -Sc 2 O 3 -Y 2 O 3 Al in the interface layer 2 O 3 fiber.

[0060] The fiber morphology obtained in this example is as follows Figure 3 As shown, compared to Figure 1 From the morphology of the original fibers, it can be clearly seen that the fiber surface is covered with a solid surface.

[0061] Example 3

[0062] (1) Take 10 g of deionized water, start stirring, weigh and add 3 g of citric acid;

[0063] (2) Weigh 16 g of zirconium oxychloride octahydrate (ZrOCl 2 8H 2 O), 1.65 g yttrium nitrate hexahydrate (Y(NO) 3 6H 2 O), adding to the product obtained in (1) and mixing uniformly to obtain a sol;

[0064] (3) Al 2 O 3 The fiber cloth is immersed in the prepared sol for one minute, and the Al 2 O 3 The fiber cloth was dried and cured in an oven at 70°C for 2 hours;

[0065] (4) The solidified Al 2 O 3 The fiber cloth was heat treated at 1100℃ for two hours to obtain ZrO 2 -Y 2 O 3 Al in the interface layer 2 O 3 fiber.

[0066] The fiber morphology obtained in this example is as follows Figure 4 As shown, compared to Figure 1 From the morphology of the fibrils, it can be clearly seen that the surface is covered with a solid surface.

[0067] Example 4

[0068] (1) Take 10 g of deionized water, start stirring, weigh and add 1 g of citric acid;

[0069] (2) Weigh 4 g zirconium oxychloride octahydrate (ZrOCl 2 8H 2 O), 0.32 g of water and scandium nitrate (Sc(NO 3 ) 3 ·xH 2 O) and 0.06 g ytterbium nitrate pentahydrate (Yb(NO 3 ) 3 ·5H 2 O), adding to the product obtained in (1) and mixing uniformly to obtain a sol;

[0070] (3) Al 2 O 3 The fiber cloth is soaked in the prepared sol for five minutes, and the Al 2 O 3 The fiber cloth was dried and cured in an oven at 70°C for 4 hours;

[0071] (4) The solidified Al 2 O 3 The fiber cloth was heat treated at 1100℃ for two hours to obtain ZrO 2 -Sc 2 O 3 -Yb 2 O 3 Al in the interface layer 2 O 3 fiber.

[0072] The fiber morphology obtained in this example is as follows Figure 5 As shown, compared to Figure 1 From the morphology of the fibrils, it can be clearly seen that the surface is covered with a solid surface.

[0073] Example 5

[0074] (1) Take 10 g of deionized water, start stirring, weigh and add 1 g of citric acid;

[0075] (2) Weigh 8 g of zirconium oxychloride octahydrate (ZrOCl 2 8H 2 O), 0.65 g of water and scandium nitrate (Sc(NO 3 ) 3 ·xH 2 O) and 0.12 g ytterbium nitrate pentahydrate (Yb(NO 3 ) 3 ·5H 2 O), adding to the product obtained in (1) and mixing uniformly to obtain a sol;

[0076] (3) Al 2 O 3 The fiber cloth is soaked in the prepared sol for five minutes, and the Al 2 O 3 The fiber cloth was dried and cured in an oven at 70°C for 4 hours;

[0077] (4) The solidified Al 2 O 3 The fiber cloth was heat treated at 1100℃ for two hours to obtain ZrO 2 -Sc 2 O 3 -Yb 2 O 3 Al in the interface layer 2 O 3 fiber.

[0078] The fiber morphology obtained in this example is as follows Figure 6 As shown, compared to Figure 1 From the morphology of the fibrils, it can be clearly seen that the surface is covered with a solid surface.

[0079] The present invention utilizes the sol method to prepare Al 2 O 3 Preparation of ZrO on fiber surface 2 -RE 2 O 3 (RE is a rare earth element) oxide layer, by chelating metal ions with citric acid to form a stable sol, mixing zirconium oxychloride and rare earth nitrate to prepare a composite oxide, soaking the fiber cloth and drying and curing, and then high-temperature heat treatment to form a dense oxide layer. This method is simple and easy to control, can be mass-produced, and significantly improves the fiber's high temperature resistance, oxidation resistance, corrosion resistance and mechanical strength, broadening its application prospects.

[0080] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing an oxide layer on the surface of a fiber, characterized in that: The following steps are involved: S1: adding citric acid as a chelating agent to deionized water and stirring, and adding zirconium oxychloride octahydrate and rare metal nitrate during the stirring process and mixing them uniformly to prepare a sol; S2: soaking the Al2O3 fiber cloth in the sol, drying and solidifying the soaked Al2O3 fiber cloth, and heat-treating the solidified Al2O3 fiber cloth to obtain Al2O3 fiber with a ZrO2-RE2O3 interface layer.

2. The method for preparing the fiber surface oxide layer according to claim 1, characterized in that: The rare metal nitrate is one or more of Sc(NO)3·xH2O, Yb(NO)3·5H2O and Y(NO)3·6H2O.

3. The method for preparing the fiber surface oxide layer according to claim 1, characterized in that: The mass ratio of the deionized water to the citric acid is 10:1-3.

4. The method for preparing the fiber surface oxide layer according to claim 1, characterized in that: The dosage of the zirconium oxychloride octahydrate is 4 to 16 g.

5. The method for preparing the fiber surface oxide layer according to claim 1 or 4, characterized in that: The mass ratio of the zirconium oxychloride octahydrate to the rare metal nitrate is 10:1-3.

6. The method for preparing the fiber surface oxide layer according to claim 1, characterized in that: The soaking time is 1 to 5 minutes.

7. The method for preparing the fiber surface oxide layer according to claim 1, characterized in that: The drying and curing time is 2 to 4 hours; the drying and curing temperature is 70°C.

8. The method for preparing an oxide layer on the fiber surface according to claim 1, characterized in that: The temperature of the heat treatment is 1100° C., and the time of the heat treatment is 2 hours.

9. An oxide layer on the surface of a fiber obtained by the preparation method according to any one of claims 1 to 8.

10. The oxide layer on the fiber surface according to claim 9, characterized in that: The oxide layer is a ZrO2-Sc2O3-Yb2O3 layer, a ZrO2-Sc2O3-Y2O3 layer or a ZrO2-Y2O3 layer.